The Scientific Kowledge of Spanish High-Speed Rail and its Relationship with Tourism through Bibliographic Analysis. - Pinos-Navarrete, Aida; Mínguez-García, Carmen (Revista de Estudios Andaluces, 2017)
The scientific production, which focused on the study of the main territorial and socioeconomic issues of the Spanish High-speed rail network, is analyzed in depth. This research aims to understand its evolution and designated topics. The results, classified by disciplines, support the hypothesis that in Spain the relationship between High-speed rail and tourism has yet to be thoroughly studied, despite its scientific and political interest. For this reason, future research must tackle a variety of questions which must be addressed through a collaboration of experts from different areas that contribute to different perspectives and methodologies.